The cultural prisons of the Arab priesthood between the restrictions of style and the looseness of the imagination - Muter, Naji Abbas (Thi Qar Arts Journal, 2022)
Semantics begin to form according to its function، then the cultural overflows it to lead it to produce meanings different from the origin of its composition، as the need forces the language to produce linguistic parallels، and the culture quickly takes it in favor of understanding the differences of its linguistic origin، so the priest started an innate need to be a representative of the sacred and a Compensated of it، but the culture has picked up the terminology to take It is far away to lead to new symbolic margins that would not have been without the cognitive and social understanding of the human being acquired new data، which became more like cultural prisons، which acquired the meaning mercurial shades that could be absorbed after the terminology was stripped of its linguistic origin and understood in light of the footnotes that were attached to it culturally ،The cultural prisons of any concept stem from the method of reception and the specificity of understanding that concerns a certain group’s extrapolation of the connotations of that concept، and Arab culture is an oral culture that dealt with concepts with a specificity that stems from the power of the place itself and its functional imperatives. Therefore، religion was for the Arab as mobile as he travels in places، so it cannot be We understand the religious orientation of the Arab unless we understand its spatial specificity.